Protein Intake, Adherence to Vitamin–Mineral Supplementation, and Dumping Syndrome in Patients Undergoing One Anastomosis Gastric Bypass - Andrade, L (2021)
Introduction: One anastomosis gastric bypass (OAGB) is an effective bariatric procedure. However, nutritional deficiencies or dumping syndrome (DS) may occur. The aim of this study was to assess adherence to nutritional recommendations and development of DS in a 3-year OAGB patient follow-up. Methods: For 150 OAGB patients, in our center, data were collected through the electronic platform and by an individual telephone interview. The inclusion criterion is OAGB as a primary bariatric procedure, no revisional surgery, or no pregnancy. The adequacy of daily protein intake cutoff was defined as 60 g. Adherence to micronutrient supplementation protocol was considered if a minimum of 5 takes/week were reported. To evaluate the occurrence of DS, the Sigstad score questionnaire was used. For statistical analysis, a significance level less than 5% (p < 0.05) was considered. Results: A total of 150 patients (80% females), BMI 44.3 ± 21.3 kg/m2, were subjected to the OAGB procedure. Of those, 128 fulfilled the study inclusion criteria. After 3 years, the mean %EBMIL was 78.4 ± 14.4. During the 3-year follow-up, the average protein intake was 60 g/day, and 48% reported an adequate daily protein intake. Adherence to the micronutrient supplementation protocol was reported by 70%. According to the Sigstad score questionnaire, DS was present in 24% of patients. Conclusion: A significant part of OAGB patients does not comply with the nutrition prescription assessed, emphasizing the need to improve team/patient communication strategies. Long-term studies are needed to characterize and assess the health impact of protein, vitamin, and mineral malnutrition in patients undergoing OAGB.